2011
DOI: 10.1007/s00404-011-2059-7
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in pregnancy. Part II: treatment options of breast and other non-gynecological malignancies

Abstract: The prognosis of the malignancy and the patient's informed consent must be taken into consideration when the well-being of the expectant mother is weighed against the well-being of the unborn child in case of maternal cancer during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Similar reports from developed countries [20] have indicated that there is no serious health-related morbidities or malignancies following exposure to chemotherapy during the second and third trimesters of pregnancy. In view of the increasing incidence of malignant disease diagnosed during pregnancy, clinical guidelines and algorithms have recently been established for diagnosis and therapy [21,22]. More studies are needed to assess the well-being of the expectant mother against the well-being of the unborn neonate in these ethically and scientiWcally challenging situations.…”
Section: Discussionmentioning
confidence: 99%
“…Similar reports from developed countries [20] have indicated that there is no serious health-related morbidities or malignancies following exposure to chemotherapy during the second and third trimesters of pregnancy. In view of the increasing incidence of malignant disease diagnosed during pregnancy, clinical guidelines and algorithms have recently been established for diagnosis and therapy [21,22]. More studies are needed to assess the well-being of the expectant mother against the well-being of the unborn neonate in these ethically and scientiWcally challenging situations.…”
Section: Discussionmentioning
confidence: 99%
“…Standard approach for breast cancer might not be suitable during pregnancy [32], since clinical experience of breast cancer in pregnant women is limited, making management decisions inevitably more complicated [12,33]. An adjustment in usual management and a modification of diagnostic methods, therapeutic tools and options is needed [33], in order to avoid possible risk to the fetus [12].…”
Section: Diagnosis Of Pabcmentioning
confidence: 99%
“…An adjustment in usual management and a modification of diagnostic methods, therapeutic tools and options is needed [33], in order to avoid possible risk to the fetus [12]. Diagnosis of PABC is based on clinical examination, imaging and histology, simi-lar to non-pregnant women [12], however, it is more difficult due to the major hormone-induced changes that occur in breast tissue, resulting in a delayed, later stage presentation, with more metastases and poorer prognosis [4,12,24,32,34]. This is of critical importance in the management of PABC.…”
Section: Diagnosis Of Pabcmentioning
confidence: 99%
“…Усе це призводить до майбутніх мультифакторіальних розладів здоров'я молодих жінок: розладів травної системи -у 22,6 %, а за даними деяких авторів, до 70 %; сечостатевої системи -у 15,0 %, органів дихання -14,8 %, системи кровообігу -13,9 % та опорно-рухової системи -22 % [39,40].…”
Section: підліткова менструальна дисфункція як маркер майбутніх розла...unclassified